Sonographic measurement of Achilles tendon thickness in seronegative spondyloarthropathies - (:unkn) unknown (My University, 2014)
OBJECTIVE: To define the best cut-off value for identifying Achilles tendon thickening using ultrasound (US) in patients with spondyloarthropathies (SpA) and to assess its diagnostic utility in comparison with different cut-off values used in the literature. MATERIAL AND METHODS: One-hundred and one subjects (55 SpA patients and 46 age and body mass index ((BMI)-matched healthy controls (HC)) were investigated. US was performed using a MyLab70 US system (Esaote Biomedica, Genoa, Italy) with a linear probe (6-18 MHz). Three images per Achilles enthesis were stored and the antero-posterior thickness of the enthesis was measured at the level of the Achilles tendon deeper margin insertion into the calcaneal bone on the longitudinal median scan. The best cut-off value for each gender was determined by ROC curve analysis and compared to the other cut-off values in the literature: 1) 5.29 mm for both genders, and 2) 5.5 mm for females and 6.2 mm for males. The number of measurements exceeding the cut-off values as well as sensitivity (SE), specificity (SP), positive (PPV) and negative (NPV) predictive values were calculated. RESULTS: A significant difference was observed for Achilles enthesis thickness between genders (mean±SD: 4.6±0.7 mm in males vs. 4.0±0.8 mm in females, p<0.00) and between SpA patients and HC (mean±SD: 4.4±0.8 mm in SpA patients vs. 4.0±0.8 mm in HC, p<0.001). The ROC curve analysis revealed the best cut-off value to be 3.7 mm for females and 4.8 mm for males (SE: 43-70%, SP: 59-85%, PPV: 66-79%, NPV: 54-63%). Previously reported cut-off values were found to have high SP (91-98%) but very low SE (2-11%). CONCLUSION: Achilles tendon thickness differs between genders; thus, it is crucial to refer to normal values that are specific for gender. High cut-off values, as previously suggested, showed very low SE in the current study. When Achilles enthesis thickening is used for the purpose of screening enthesitis in SpA patients, a lower cut-off value has a higher SE with slightly worse SP, PPV and NPVs.
Keywords: ultrasound; Achilles tendon thickness; enthesitis; seronegative spondyloarthropathies